Придавката Liber и нејзините изведенки во игрите со зборови кај Плаут - Џукеска, Елена (Филозофски факултет - Скопје, 2016)
The adjective līber, „free, released, loose, unoccupied“ from the Indoeuropean root *H1leudh-, „grow“ and its derivatives lībertas, „freedom“, lībertus and lībertīnus, „freedman“, lībero, „free“, līberālis, „free, noble, generous“, līberī, „children“, Līber, „Liber, Liberator“ play significant role in creating wordplays in the works of the Roman comediographer Plautus. The analysis of the examples shows that these words on one hand were used by Plautus for creation of funny situations of misunderstanding, based on their polysemy. On the other hand Plautus puts them in a context with other words, that are not etymologically related, by sound similarly. This second type of wordplays is important testimony for the semantical development of the adjective līber and its derivatives in Old Latin, but also for an additional analysis of the understanding of the term „freedom“ by Latins.
The adjective ‘liber’ and its derivatives in Plautus' word plays
Keywords: Liber, Plautus, wordplay